Counter Radicalism Policy in University - Nurdin, Encep Syarief; Nurbayani, Siti; Rahmat, Rahmat; Tanshzil, Sri Wahyuni (Jurnal Civicus, 2023)
The rise of radicalism in the campus environment has raised a lot of attention from various groups. The massive and structured movement, reinforced by propaganda through social media, has become the many factors that have resulted in the emergence and development of this movement on campus. Therefore, campuses need to take counter-radicalism policies through various structured patterns and involve the entire academic community. This study uses a mix method approach, combining qualitative and quantitative approaches. The method used is sequential exploratory, which is a research method that begins with qualitative methods, namely collecting, studying, analyzing qualitative data, then carrying out quantitative studies and data analysis on 269 students at the Indonesian University of Education. The results of the research prove that the Indonesian University of Education chooses a policy pattern that is represented in three main areas, namely: 1) curriculum and learning, 2) student affairs and Student Organizations, and 3) Habituation of anti-radicalism values in the campus environment. This pattern is carried out simultaneously and comprehensively because it involves the entire UPI academic community.